Quality of life in dialysis: a Malaysian perspective - Liu, Wen Jiun; Musa, Ramli; Chew, Thian F.; Lim, Christopher Thiam Seong; Morad, Zaki; Bujang, Adam Mohamad (Blackwell Publishing Inc., 2014)
There is a growing interest to use quality of life as one of the dialysis outcome measurement. Based on the Malaysian National Renal Registry data on 15 participating sites, 1569 adult subjects who were alive at December 31, 2012, aged 18 years old and above were screened. Demographic and medical data of 1332 eligible subjects were collected during the administration of the short form of World Health Organization Quality of Life questionnaire (WHOQOL-BREF) in Malay, English, and Chinese language, respectively. The primary objective is to evaluate the quality of life among dialysis patients using WHOQOL-BREF. The secondary objective is to examine significant factors that affect quality of life score. Mean (SD) transformed quality of life scores were 56.2 (15.8), 59.8 (16.8), 58.2 (18.5), 59.5 (14.6), 61.0 (18.5) for (1) physical, (2) psychological, (3) social relations, (4) environment domains, and (5) combined overall quality of life and general health, respectively. Peritoneal dialysis group scored significantly higher than hemodialysis group in the mean combined overall quality of life and general health score (63.0 vs. 60.0, P < 0.001). Independent factors that were associated significantly with quality of life score in different domains include gender, body mass index, religion, education, marital status, occupation, income, mode of dialysis, hemoglobin, diabetes mellitus, coronary heart disease, cerebral vascular accident and leg amputation. Subjects on peritoneal dialysis modality achieved higher combined overall quality of life and general health score than those on hemodialysis. Religion and cerebral vascular accident were significantly associated with all domains and combined overall quality of life and general health.